Transformation of East Kalimantan Batik into Ready-to-Wear Fashion with Augmented Reality for Creative Economy IKN - Putri, Hesti Rosita Dwi; Yendra, Sasferi; Syaputra, Eko Agung (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The uniqueness of East Kalimantan batik lai in its motifs and colors which are influenced by motif designs inspired by the Dayak tribe, local flora, and fauna. The transformation of East Kalimantan batik into ready-to-wear fashion is a strategic initiative to combine cultural heritage with modern design trends, and contribute to the creative economy in Indonesia's new capital city. This research explores the development of batik from a traditional fabric into a contemporary fashion product, with the aim of strengthening local identity so as to expand market reach. Augmented reality technology is used to enhance the consumer experience through a virtual try-on feature, allowing users to view batik clothing in real time. The problem formulation in this research is how the transformation process of East Kalimantan Batik into ready-to-wear fashion products, and how the use of Augmented Reality technology can provide solutions to improve user experience in trying and deciding product purchases effectively. The method used is the Design Thinking method which is carried out with 4 stages namely discover, define, develop and deliver. The results obtained Augmented Reality in the promotion of ready-to-wear batik not only supports the preservation of local culture, but also strengthens the competitiveness of batik products in the modern era. This is an important step in making batik a highly competitive ready-to-wear fashion product in supporting IKN's creative economy.